Implementasi Metode Problem Solving Pada Materi Pengukuran Panjang dan Berat di SD Kelas 3 - Bebun Sayati; Nur silawati; Fahrenza Dyan Nabilah; Muh Royyan Ramadani; Nur Wiji Sholikin (PT Cendekia Education Center, 2026)
This study aims to describe the implementation of the problem-solving method in learning measurement of length and weight for third-grade elementary school students and to determine ist effect on students’ learning outcomes and participation. The background of this study is based on the low understanding of students regarding measurement concepts due to teacher-centered learning and the lack of student involvement in solving real-life problems. The problem-solving method was chosen because it can train students to think critically, actively participate, and develop skills in solving problems related to daily life. This study used a descriptive qualitative approach with third-grade elementary school students as the research subjects. Data collection techniques included observation, interviews, documentation, and learning outcome tests. The results showed that the implementation of the problem-solving method improved students’ understanding of length and weight measurement concepts. Students became more active in discussions, were able to cooperate effectively in groups, and showed greater confidence in expressing opinions and providing solutions to the given problems. In addition, students’ learning outcomes increased after the implementation of the method. Therefore, the problem-solving method is considered effective for mathematics learning, especially in the topic of measuring length and weight for third-grade elementary school students.